PENGEMBANGAN TEKNIK PRODUKSI MASSAL BIOMAS ECENG GONDOK - Tatuk Tojibatus Sa’adah; Dwi Haryanta (Journal of Research and Technology, 2016)
Siltation and the presence of water hyacinth plants on a sewer/river is a cause of flooding in urban areas (beaches). Water hyacinth grows fast in rivers, sewer, boezem, lake and or water storage areas, which impedes the water flow and encourages a silting. Rivers dredging or reservoirs of waste water hyacinths just stacked on the edge of river that makes the dirty environment. The research aims to develop a composting technique made from water hyacinth in a mass scale. Factorial experimental treatments (1) Packaging B1: open, B2: plastic bags (glangsing), and B3: buried; and (2) Starter S1: mixture EM4 30%, S2: mixture EM4 20% + urea 1kg/3 liter, and S3: mixture EM4 10% + urea 2 kg/3 liter, so there are nine treatment combinations. Experimental units are water hyacinth biomass as much as one cubic, nine cubic overall. The research results devoted to volume shrinkage, variable temperature, pH, change in smell, colour and biomass texture of water hyacinth during the first two weeks showed a high variation among treatments, but in the fifth week, all of variables were homogeneous relatively and showed almost complete indicators of composting process. Depreciation amounted to 68-78% volume, temperature 26-29oC, pH of 7.0-7.5; texture is brittle, blackish brown color and relatively odorless. C/N biomass ratio at composting mass of water hyacinth from 33-37, and at fifth week the results are varied for the treatment of S1, S2B1, and S3B1 value is still above 20 while the other is below 20, and the lowest at 16.9 S3B3 treatment. Keywords: Composting technology mass, Water hyacinth biomass, Starter, Packaging